RACMO2.3p3 monthly SMB, SEB, t2m and t10m data for Greenland (September 2000-2018) ... - van Dalum, Christiaan; van de Berg, Willem Jan; van den Broeke, Michiel (Zenodo, 2020)
This data set contains RACMO2.3p3 (Rp3) output between September 2000 to 2018 and RACMO2.3p3 without energy absorption (Rp3 WIE) output between September 2000 to 2015 for Greenland at 11 km. Netcdf files are provided for monthly-accumulated (monthlyS) and monthly-averaged (monthlyA) data for the surface mass balance (SMB), surface energy budget (SEB) and temperature. The following parameters are included: 2-m air temperature (t2m), 10-m depth snow temperature (t10m), shortwave downward radiation (swsd), net shortwave radiation (swsn), longwave downward radiation (lwsd), net longwave radiation (lwsn), sensible heat flux (senf), latent heat flux (latf), surface mass balance (smb), precipitation (precip), refreezing (refreeze), sublimation (subl), drifting snow erosion (sndiv), runoff and snow melt. In addition, the topography and ice mask are added in a separate file. This data set is used in the manuscript "Impact of updated radiative transfer scheme in RACMO2.3p3 on the surface mass and energy budget of the ...